ESTIMATION OF WORKING CAPACITY AMONG WORKERS WITH ALLERGIC CONTACT DERMATITIS IN THE TEXTILE INDUSTRY - Nedeva, Marija; Cifrevska Matevska, Vesna; Bajić, Lazar (Acta medicae Medianae, 2026)
Working capacity is the physical, mental and intellectual capacity of the worker to perform certain work duties under specific conditions, all the while without harming their health. Should the sensitized person have repeated contact with a potential sensitizer during the performance of those duties, occupational allergic contact dermatitis may occur—skin inflammation of the eczema type, which can impact working capacity and even fully incapacitate the individual from performing those work duties. The aim of this paper was the estimate of the working capacity of 98 examined workers in the textile industry, 9 of whom have been diagnosed with allergic contact dermatitis. The medical part of the expertise for the estimate of working capacity encompassed a precise and comprehensive allergologic history, positive patch tests to certain potential allergens and responses to exposure—elimination test. The practical part of the estimate of the working capacity demanded a full job description, as well as a description of the conditions in which the specific job was performed. In estimating the working capacity of a patient with occupational contact dermatitis, we kept in perspective the psycho-social approach of the affected person, including their age, level of professional qualification, and the likelihood that the company would accept the suggestions given by medical and other professionals. Every case where we performed an estimate of the working capacity was done in isolation and with due respect for the individual.